Implementation of Career Information Services in Choose Department in Higher Collection in MAN 2 Cirebon - Faisal, Sopyan; Sulistianingsih, Sulistianingsih; Isnaeni Fajri, Rizqi; Ridwan, Taufik (Journal of World Science, 2022)
Education at the high school level aims to prepare students who will continue their education to a higher level, as well as prepare students who will immediately work when they have completed high school education. Experience in the field shows that there are still many MAN 2 Cirebon students who are still confused about choosing a major or study program to enter in higher education, especially for class XII students. Students make career plans based only on their will and desire without considering their abilities, there are even some students who leave career choices to their peers or other people. The purpose of this study was to determine the implementation and provision of career information services in choosing majors in higher education at MAN 2 Cirebon and the factors that became obstacles in these services. This study uses a descriptive qualitative research method with a phenomenological approach. This study relies on the accuracy of data collection to obtain valid research results. Data collection techniques in this study used observation, interviews, and documentation of the implementation of career information services in choosing majors in higher education at MAN 2 Cirebon. The validity of the data uses data triangulation. Based on the research that has been done, it is found that the implementation of career information services in choosing a major in higher education at MAN 2 Cirebon is very useful and has an effect on students' interest in continuing to college. This can be seen from the data of students who are accepted into universities from year to year which has increased quite a bit. The implementation of career information services in choosing majors in higher education at MAN 2 Cirebon makes researchers pay special attention so that researchers conduct research by taking that title.